Utility of preoperative 3 Tesla pelvic phased-array multiparametric magnetic resonance imaging in prediction of extracapsular extension and seminal vesicle invasion of prostate cancer and its impact on surgical margin status: Experience at a Canadian academic tertiary care centre - Lee, Taehyoung; Hoogenes, Jen; Wright, Ian; Matsumoto, Edward D.; Shayegan, Bobby (Canadian Urological Association Journal, 2017)
Introduction: To evaluate the utility of 3 Tesla (3T) pelvic phased-array (PPA) multiparametric magnetic resonance imaging (mpMRI) to predict extracapsular extension (ECE) and seminal vesicle invasion (SVI) and its subsequent effect on radical prostatectomy (RP) surgical margin status. Methods: A retrospective evaluation was conducted of RP patients who underwent preoperative 3T PPA mpMRI (without endorectal coil) based on clinical probability of adverse pathological features. Frequencies, specificity, sensitivity, positive predictive value (PPV), and negative predictive value (NPV) of mpMRI in predicting the status of ECE and SVI were calculated. Results: Forty-eight consecutive patients were included. Sensitivity, specificity, PPV, and NPV for 3T PPA mpMRI using T2-weighted sequences with diffusion-weighted imaging (DWI) and dynamic contrast enhanced (DCE) imaging to predict ECE was 39%, 56%, 45%, and 50%, respectively, while SVI prediction was 33%, 95%, 50%, and 91%, respectively. Twelve of the 28 cases predicted as being negative for ECE had positive margins, while two of the 20 cases predicted to be positive for ECE had positive margins. Imaging predicted four cases would have SVI, yet two had positive margins, while of the 44 cases predicted as being negative for SVI, four had positive margins. Conclusions: These findings at our centre suggest that the use of 3T PPA mpMRI using T2-weighted sequences with DWI and DCE in predicting pathological ECE and SVI is of questionable benefit. These mpMRI reports may result in closer dissection of neurovascular bundles and subsequent positive surgical margins. Caution should be exercised when basing intraoperative decisions on mpMRI findings.